Free bednets to pregnant women through antenatal clinics in Kenya: a cheap, simple and equitable approach to delivery. - Guyatt, H; Gotink, M; Ochola, SA; Snow, R (2002)
Kenya's National Malaria Strategy states that insecticide-treated nets (ITNs) would be considered as a free service to pregnant women assuming sufficient financial commitment from donors. In 2001, United Nation's Children's Fund (UNICEF) and the Government of Kenya brokered support to procure and distribute nets and K-O TABs (deltamethrin) to 70 000 pregnant women in 35 districts throughout Kenya around Africa Malaria Day. This intervention represented the single largest operational distribution of ITN services in Kenya to date, and this study evaluates its success, limitations and costs. The tracking process from the central level through to antenatal clinic (ANC) facilities suggests that of the 70 000 nets procured, 37 206 nets (53%) had been distributed to pregnant women throughout the country within 12 weeks. One-fifth of the nets procured (14 117) had gone out to individuals other than pregnant women, most of these at the request of the district teams, with only 2870 nets estimated to have gone astray at the ANC facilities. At 12 weeks, the remaining 18 677 nets were still in storage awaiting distribution, with more than two-thirds having reached the district, and nearly half already being held at ANC facilities. The cost of getting a net and K-O TAB to an ANC facility ready for distribution to a pregnant woman was US$ 3.81. Accounting for the 14 117 nets that had gone to other users, the cost for an ITN received by a pregnant woman was US$ 5.26. Delivering ITNs free to pregnant women through ANCs uses an existing system (with positive spin-offs of low delivery cost and simple logistics), is equitable (as it not only targets those who can afford it) and can have the added benefits of strengthening ANC service, delivery and use.